Mathematical Self-Esteem of Junior High School Student based on Gender - D Fisher; Y S Kusumah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The formulation of the national education paradigm of the 21st century that education should be oriented to the science of mathematics and natural sciences. Mathematics is one field of science that helped determine and support the progress of science and technology. In studying mathematics, there are still many students both male and female who view mathematics as a boring subject. Based on that, the gender aspect in the learning of mathematics became the attention of educators. Gender differences not only result in different abilities in mathematics, but also how to acquire mathematical knowledge. This research is a qualitative descriptive research which aims to describe students' self-esteem mathematics based on gender and its relationship with mathematics achievement. A total of 72 female students and 68 male students became respondents in this study. The results showed that male students had higher levels of mathematical self-esteem compared to female students and mathematical self-esteem had a positive relationship to student achievement.